Rancang Bangun Sistem Hidrolik Buka Tutup Palka secara Otomatis dan Manual Berbasis IoT - Fahad Abdulloh Bin Ahmad; Edi Kurniawan (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
This study aims to design and build a hydraulic system capable of operating hatch opening and closing automatically and manually, with the application of Internet of Things (IoT) technology to monitor and control the system remotely. This system is designed to improve efficiency and ease of hatch operation on ships or other industrial applications, as well as prevent fires in cargo due to several factors such as unintentional negligence of the ship's crew and also weather factors with increasing temperatures. Where the automatic system uses a rain sensor to optimize time and energy, while manual control remains available as a backup option. This design involves the integration of hydraulic actuators, rain drop sensors, microcontrollers, and IoT communication modules that allow users to control and monitor the position of the hatch through a web-based application or mobile device. In compiling this scientific paper, researchers use experimental methods. This study shows the results that testing will be carried out directly by researchers, by testing the performance of the prototype of the automatic and manual hatch opening and closing hydraulic system design tool based on IoT by testing the effectiveness of the control system and sensor performance. In conclusion, this system successfully combines hydraulic and IoT technology to create an efficient, safe, and easy-to-use solution in practical applications.